Práticas de Leitura no Maranhão na Primeira República: entre apropriações e representações - Castellanos, Samuel Luis Velázquez (2007)
The main goal of this investigation was to understand the relational weaving of reading practices among teachers from São Luís do Maranhão, exploring multiple aspects that have contributed to their education as readers as well as the implications as such aspects on teachers pedagogical practices (ZILBERMAN; LAJOLO, 1990; HALLEWELL, 2005; CASTRO, 2007). It studied the socio-historical field of education in Maranhão in the first decades of the XX century, highlighting questions raised from the examination of printing material and its diverse appropriations. It also analysed, described and assessed teaching and learning of reading practices and students reading behaviour through the notions, conceptions and narratives of teachers about their educational praxis in which they acted and interacted (ANDRADE, 1984; SALDANHA, 1992; NÓVOA, 1995; GOODSON, 1995; WOODS, 1995; MOTTA, 2003). The goal was to unveil strategies, developments and transformations in diverse ways of appropriations of teachers as readers cultural production, and its influence in the educational process and in the reading education of their students in the school context (CERTEAU, 1982, 1996; CHARTIER, 1994, 1996, 2003; ABREU, 2003). It highlights through life stories of teachers, using their memory as instruments of analysis (THOMPSON, 1992; BOSI, 1994; BOBBIO, 1997; LE GOLF, 1987) diverse changes to which they were subject in their ways of reading, the appropriation of meaning from text, the production, circulation and distribution of printing material. It employed cultural history (CHARTIER, 1988; BURKE, 2005; HUNT, 1992) as an analytical axes of reflection and a qualitative approach of investigation, supporting our analysis of oral history, focusing on the reminiscences, intertextualities and voices of teachers, through open interviews in the beginning and semi-structured interviews following, which were designed in circles (BAKHTIN, 1988, BOUMARD, 1999) and, had the assistance of participant observation, finding ways to interpret the exposed interpretations by those producers of culture being studied, through different cultural lenses (LAPASSADE, 1993 apud FINO, 2006; ERICKSON, 1999; BARROS, 2004; MATTOS, 1995). It argues for an analysis of collective and individual memory of men and women located in a certain moment, space and field of action in which local identities are perpetuated. It compares their life histories and their reading practices in different political, economical, cultural and educational moments, having as differential categories a priori issues of gender, ethnicity, identity, social class and geographic location (HALL, 2000; BAUMAN, 1998; ELIAS, 1994; GIDDENS, 2002; SILVA, 2000). To analyse and interpret these multiple determinations involved in the process of appropriation of reading, expressed through the conceptions, notions and visions of educators in their field of action and in their pedagogical activities in the school context, will allow the acquisition of cultural productions of these consumers of culture connected to different types of relations, interactions and activities performed in the social tissue, understanding their roles as readers and their educational practices as mentors of new readers, merging spaces of production and circulation of printed materialities, in a direct interaction with the political scenario that, in spite of being located in Maranhão, express a national way of thinking and feeling.